Digital technologies in basic education and the territorialization of inequalities: The case of Amazonas (Revista Contexto & Educação, 2025)
This study analyzes the application of Digital Information and Communication Technologies (DITs) in basic education in the state of Amazonas, with an emphasis on the territorialization of educational inequalities. Based on the analysis of the "Aula em Casa" project — implemented by the Government of Amazonas during the COVID-19 pandemic — and official data, such as the institutional dashboard of SEDUC-AM (2020), strong asymmetries in the distribution and use of technologies between the capital and the interior were identified: while management reached 88.68% in the capital, in the interior it was restricted to 39.26%. WhatsApp was the most used resource, with 162,083 participants, in contrast to the 28,491 who accessed Google Classroom, evidencing the prevalence of more accessible but less sophisticated pedagogical tools. The article highlights that only 4% of public schools in Amazonas joined the Connected Education Innovation Program (PIEC), revealing the mismatch between national public policies and regional realities. Furthermore, data from 2022 show that 40.9% of the state's public schools still do not have internet access (ANATEL, 2022), with the situation being most serious in riverside areas, where 97% of institutions remain disconnected (FAS; UNICEF, 2017). The study concludes that, although ICTs are potentially democratizing, their implementation in the Amazon is limited by structural, geographic, and historical factors. Thus, it is argued that there is a need for territorially sensitive educational policies, with structural investments, adequate teacher training, and integration of local knowledge, so that digital technologies can effectively become instruments of inclusion and educational justice.
Keywords: Digital technologies; basic education; educational inequalities; Amazonas; public policies